Denitrification dynamics in unsaturated soils with different porous structures and water saturation degrees: A focus on the shift in microbial community structures - 오성직; 조경진; Park, Saerom; Kwon, Man Jae; Chung, Jaeshik; Lee, Seunghak (Elsevier BV, 2023)
Despite its environmental significance, little is known about denitrification in vadose zones owing to the complexity of such environments. Here, we investigated denitrification in unsaturated soils with different pore distributions. To this end, we performed batch-type denitrification experiments and analyzed microbial community shifts before and after possible reactions with nitrates to clarify the relevant denitrifying mechanism in the microcosms. For quantitative comparison, pore distribution in the test soil samples was characterized based on the uniformity coefficient (Cu) and water saturation degree (SD). Micro-CT analysis of the soil pore distribution confirmed that the proportion of bigger-sized pores increased with decreasing Cu. However, oxygen diffusion into the system was controlled by SD rather than Cu. Within a certain SD range (51？67%), the pore condition changed abruptly from an oxic to an anoxic state. Consequently, denitrification occurred even under unsaturated soil conditions when the SD increased beyond 51？67%. High throughput sequencing revealed that the same microbial species were potentially responsible for denitrification under both partially (SD 67%), and fully saturated (SD of 100%) conditions, implying that the mechanism of denitrification in a vadose zone, if it exists, might be possibly similar under varying conditions.